Independent evolutionary lineage of the clingfish Gobiesox adustus (Gobiesocidae) from Isla del Coco, Costa Rica - Torres Hernández, Eloisa (2020)
Introduction: Isla del Coco is an important protected area for marine fauna in the Eastern Tropical Pacific. In this area, the species that inhabit the intertidal zone have been subject to few studies. One of the species inhabiting these areas is the clingfish Gobiesox adustus (Gobiesocidae). Objective: To analyze for the first time the mitochondrial gene cytochrome oxidase subunit 1 (cox1) of G. adustus’ population from Isla del Coco and compare it with those of continental coast of Costa Rica and Ecuador. Methods: We constructed a haplotype network for these samples. Genetic diversity, distance and structure were calculated by several software. The historical demography of Isla del Coco samples was assessed with the method Bayesian skyline plot as implemented in BEAST2. Results: The samples segregate into three haplogroups: one consisting of the Isla del Coco samples, a second consisting of a subset of the Ecuador samples, and a third consisting of Costa Rica and the remaining Ecuador samples. The genetic distances between the three haplogroups range between 1.6% and 2.1% (uncorrected p-distance), and pairwise ΦST and AMOVA results between the three haplogroups show high and significant values. Conclusions: The Isla del Coco haplogroup showed a Pleistocene population growth, which agrees with demographic patterns found in other marine organisms. The history of isolation of the G. adustus population from Isla del Coco demonstrates the evolutionary independence of this population.